PENGARUH DIVERSITAS DEWAN DIREKSI TERHADAP NILAI PERUSAHAAN - Pramesti, Aryanti Ariesta; Nita, Riski Aprillia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
The diversity of gender, age, tenure, educational background and nationality are factors that companies must consider when selecting someone to serve on the company's board of directors. The purpose of this study is to analyze the effect of board of directors diversity on firm value. This research was conducted on Property, Real Estate, and Building Construction sector companies listed on the Indonesia Stock Exchange in 2016-2020. The sample of this study was selected using purposive sampling. This study obtained data from 56 companies with a total sample used in this study as many as 236 companies. Testing this hypothesis using multiple linear regression test with SPSS software version 24. The results showed that gender diversity, educational diversity and tenure diversity had an effect on firm value, while age diversity and nationality diversity had no effect on firm value.